New ways of thinking about research on class size: an international perspective. Introduction to the special section. (2019) - Blatchford, Peter; Russell, Anthony
Highlights: Current understanding of class size limited to Western countries. This special section extends understanding of class size effects. Introduces new studies of class size effects in Europe. Introduces new studies of classroom processes related to class size. Introduces new studies on professional development to support class size changes. Abstract: Debate about class sizes in schools is long standing and contentious. In this review we show much research is limited and outdated, with an exclusive concern with pupil academic outcomes. This Special Section seeks to extend the literature on class size in two ways. First, it addresses what goes on in classrooms which might account for any effects found, and it also examines professional development approaches to making the most of teaching opportunities afforded by class size. Second, it reflects the shift of research on class size from the USA and the UK to elsewhere in Europe and in East Asia. This Section aims to provide a timely and significant advance on the rather tired debate over class size.